Penguatan Manajemen Lembaga Pendidikan Anak Usia Dini (PAUD) di Desa Garawangi dan Desa Rancaputat Kecamatan Sumberjaya Kabupaten Majalengka - Firmansyah, Egi Arvian; Wardhana, Wardhana (LP2M IAIN kUDUS, 2016)
The institutions of ECD (Early Childhood Development) have a vital role in a nation education sector because they are the very first institutions to instill educational values to learners, either religious values or universal values. The management of ECD institutions has been seemingly considered less important or less prestigious compared with the management of higher education institutions such as high school or university level. This paper portrays the activity results of Community Service Program focusing on early childhood development in the Garawangi and Rancaputat village, Sumberjaya District, Majalengka. This paper is expected to increase the awareness of all parties regarding the importance of early childhood education management, particularly in financial management aspect. In addition, it is expected to add insight about the Community Service Program with a focus on small institution in village such as early childhood development. Keywords: early childhood development, Garawangi, Rancaputat, Financial Management of Small Institutions